PERANCANGAN APLIKASI MOBILE JEJARING SOSIAL MASJID UNTUK PENGEMBANGAN WIRAUSAHA - Wijaya, Kurnia Pitri; Wahjudi, Deddy (Narada : Jurnal Desain dan Seni, 2022)
The mosque is a gathering center for Muslims in worship activities. However, the truth is that the mosque is not only a place of worship but also a center for development, including economic development. With the development of digital technology, Muslims must be able to adapt. One way is to optimize the mosque as a center for economic development. At present the economic potential that exists in the congregation and also the environment around the mosque cannot be utilized well. Prospering the mosque can also be interpreted as economically prosperous for the congregation and the networks around it. Through media design in the form of application-basedmobile, this potential can be optimized. The design method used in this research isdesign thinking. The research begins with exploring the problems and needs of users with the output being the design of application mediamobile to answer the needs of these users. The purpose of the designed media is to develop entrepreneurship from mosque social networks. So that the mosque becomes the center of economic development from the social networks around it. From the results of the analysis of the data obtained, it is known that users will choose to shop through mosque social networks if there is adequate information about this. So far, there has been no link between demand and supply among fellow mosque congregations, so there has been no economic interaction in it. Respondents also said they were interested in becoming entrepreneurs but had limited knowledge, expertise and resources. The designed application is tested on users and measured using the method System Usability Scale (SUS). The results of trials conducted on users show that the application gets a value of 71.75 or is included in the good category